2017
DOI: 10.1038/nature21061
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular mechanism for the regulation of yeast separase by securin

Abstract: Separase has a critical role in dissolving the cohesion among sister chromatids during chromosome segregation 1–7. Separase is over-expressed in human tumors, making it a potential target for drug discovery 8. The protease activity of separase is strictly regulated by the inhibitor securin, which forms a tight complex with separase and may also stabilize this enzyme 9–16. Separases are large, 140–250 kD enzymes, with an N-terminal α-helical region and a caspase-like catalytic domain (CD) at the C-terminus. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 39 publications
(49 reference statements)
2
44
0
Order By: Relevance
“…PP2A Cdc55 regulates Pds1 phosphorylation status both in unperturbed and replication stress conditions specifically at CDK consensus sites necessary for its Esp1 interaction. Recent studies showed that the Pds1 C-terminal segment (residues 258-373) is required for the Esp1 interaction, which is consistent with the idea that phosphorylation at the C-terminal sites located at S277, S292, T304 are required for Esp1 binding (47). They propose a model that S277 should have favorable interactions with Esp1 due to a possible conformational change induced by S292 and T304 phosphorylation.…”
Section: Pp2a Cdc55 Disrupts the Pds1-esp1 Interactionsupporting
confidence: 70%
See 1 more Smart Citation
“…PP2A Cdc55 regulates Pds1 phosphorylation status both in unperturbed and replication stress conditions specifically at CDK consensus sites necessary for its Esp1 interaction. Recent studies showed that the Pds1 C-terminal segment (residues 258-373) is required for the Esp1 interaction, which is consistent with the idea that phosphorylation at the C-terminal sites located at S277, S292, T304 are required for Esp1 binding (47). They propose a model that S277 should have favorable interactions with Esp1 due to a possible conformational change induced by S292 and T304 phosphorylation.…”
Section: Pp2a Cdc55 Disrupts the Pds1-esp1 Interactionsupporting
confidence: 70%
“…They propose a model that S277 should have favorable interactions with Esp1 due to a possible conformational change induced by S292 and T304 phosphorylation. When Pds1 and Esp1 are bound, the Pds1 C-terminal region is located in the Esp1 active site (47). While this explains how Pds1 may block Esp1 protease activity, it remains unclear if the interaction site affects Esp1 function in spindle elongation.…”
Section: Pp2a Cdc55 Disrupts the Pds1-esp1 Interactionmentioning
confidence: 99%
“…Pds1 is highly unstructured, but when bound to Esp1 they together form an elongated shape. However a crystal structure of Pds1 bound to Esp1 only resolved residues 258-373 bound to Esp1's protease site, leaving open the possibility that the C-terminal of Pds1 may have flexibility to interact with other proteins while still inhibiting Esp1's activity (51).…”
Section: Discussionmentioning
confidence: 99%
“…MultiBac was first adopted by the structural biology community and has enabled structure elucidation of many multiprotein complexes, illuminating their cellular functions. Here, we show a selection of recent structures obtained with MultiBac-produced specimens [22][23][24][25][26][27][28][29][30][31] (Fig. 2).…”
Section: Accelerating Multiprotein Complex Structural Biologymentioning
confidence: 99%
“…Multiprotein complex structural biology. A selection of recent near-atomic structures of MultiBac-produced specimens, determined by X-ray crystallography or electron cryo-microscopy[22][23][24][25][26][27][28][29][30][31]. In the case of mTOR complex 1, heterologous Raptor was produced by using MultiBac and crystallized, and the crystal coordinates fitted into a cryo-EM map of endogenously purified holo-complex in a hybrid approach[31].…”
mentioning
confidence: 99%